WIDOWHOOD RITUALS: A GENDERBASED VIOLENCE AGAINST THE DIGNITY AND RIGHTS OF WOMEN IN NIGERIA - Ojo, Anthonia Bolanle (Asian Horizons, 2019)
Gender-Based Violence (GBV) remains one of the most serious threats to women, most especially the widows in Africa, particularly in Nigeria. Widows have often been faced with traumatic experiences in African communities at the instance of losing their husbands which is occasioned by death. In Africa, widows go through a lot of hardship that stems from the society, the husband’s family and from tradition. The inhuman treatment meted on the widows are carried out as part of culture, and the rituals vary from one culture to the other. Most of the treatments are geared towards dehumanizing their victims which is always a painful and psychological experience that can affect the individual throughout her lifetime. It is an infringement on the rights of the widows as human beings created in the image and likeness of God. This paper, focusing on the plight of widows in Africa in general and Nigeria in particular, establishes the fact that widowhood rituals is a form of gender-based violence against women which dehumanizes them, and perhaps one of the most prevalent violation of human rights experienced today. It looks at an array of harmful widowhood rites in Africa and how gender and its attendant problems hamper the woman’s human rights. It also analyses the teaching of the Catholic Church on human rights. It is believed that if women are empowered through education aimed at improving their knowledge about their rights, there will be increasing opportunities to liberate themselves from the violence against them.